Promises Unfulfilled: Right-to-Work's Early Economic Track Record in Indiana. (December 2015) - Manzo, Frank
This article examines the early economic track record of Indiana's "right-to-work" (RTW) law on labor market outcomes. It analyzes various labor market metrics to compare the experience in Indiana relative to nine neighboring states, as well as to the United States in the aggregate. Data are analyzed both 36 months before and 36 months after Indiana passed RTW. Initial "difference-in-difference" estimates find that the labor market performance of Indiana has not surpassed that of neighboring states following passage of the law, contrary to the claims promised by its proponents. Wage and employment growth in Indiana's construction industry, in particular, has fallen significantly behind the rest of the region. Regression analyses are subsequently performed, which conclude that RTW's unique effect has been to lower hourly wages in the state economy by 1.1 to 1.5 percent on average and have little to no impact on employment. The combination of effects results in state income tax revenues that are annually $16 to $52 million lower than they would be in the absence of the RTW policy.